2020
DOI: 10.1002/jmv.25761
|View full text |Cite|
|
Sign up to set email alerts
|

The potential chemical structure of anti‐SARS‐CoV‐2 RNA‐dependent RNA polymerase

Abstract: An outbreak of coronavirus disease 2019 (COVID-19) occurred in Wuhan and it has rapidly spread to almost all parts of the world. For coronaviruses, RNAdependent RNA polymerase (RdRp) is an important protease that catalyzes the replication of RNA from RNA template and is an attractive therapeutic target. In this study, we screened these chemical structures from traditional Chinese medicinal compounds proven to show antiviral activity in severe acute respiratory syndrome coronavirus (SARS-CoV) and the similar ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
239
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 252 publications
(245 citation statements)
references
References 17 publications
2
239
0
4
Order By: Relevance
“…is -5.16 kcal/mol (15). In our previous study, we discovered that theaflavin (ZINC3978446) is a potential chemical structure of anti-SARS-CoV-2 RNA-dependent RNA polymerase (9). Moreover, we also found that theaflvin was able to dock in contact area in RBD of SARS-CoV-2.…”
Section: The Docking Binding Energy Between Dihydrotanshinone I and Smentioning
confidence: 91%
See 1 more Smart Citation
“…is -5.16 kcal/mol (15). In our previous study, we discovered that theaflavin (ZINC3978446) is a potential chemical structure of anti-SARS-CoV-2 RNA-dependent RNA polymerase (9). Moreover, we also found that theaflvin was able to dock in contact area in RBD of SARS-CoV-2.…”
Section: The Docking Binding Energy Between Dihydrotanshinone I and Smentioning
confidence: 91%
“…In a recent study, we discovered that theaflavin possesses a potential chemical structure of anti-SARS-CoV-2 RNA-dependent RNA polymerase (9). Some Chinese medicinal compounds are also used for prophylaxis of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies report on SARS-CoV-2, as expected given the short time since its emergence. However, a number of studies report on use of computer modelling for screening purposes (Liu and Zhou, 2005;Lung et al, 2020;Toney et al, 2004;Wang et al, 2007;Zhang et al, 2020). Typically, these models determine the free binding of energy between a ligand and a receptor (Forli et al, 2016), with a lower free binding energy indicating a stronger bond between the ligand and receptor.…”
Section: Inhibitors Of Sars-cov-2 (Covid-19)mentioning
confidence: 99%
“…Theaflavin and its derivatives have also been shown to be equally effective as an antioxidant in comparison with catechins (40). Furthermore, it was shown to have lower docking scores against RNA dependent RNA polymerase of SARS-CoV-2 in a recent study (41). Though the most important finding was a strong hydrogen bond between its hydrogen (H8) and oxygen of His41 residue which also serves a critical role in forming the active catalytic site.…”
Section: Main Protease (Mpro Also Called 3cl Pro) (Pdb Code 6w6y)mentioning
confidence: 99%